The role of integrated prawn farming in climate change adaptation in Bangladesh: ecosystem services, economic viability and barriers - Rahman , Md. Asadur; Alam, Md. Mehedi; Sakib, Sadman; Das, Rupesh; Faruque, Md. Hasan (Journal of Fisheries, 2025)
The integrated rice-prawn-vegetable culture (RPVC) is an effective farming method that ensures the efficient utilization of water and land. This study aims to evaluate the role of RPVC in climate change adaptation, its ecosystem services, and economic sustainability in Bangladesh. Integrated RPVC provides farmers with ecosystem services, including reducing use of the fertilizers and insecticides and lowering financial instability. The vegetable platform shades prawn ponds naturally, while prawns consume insects in rice fields. After rice plants are harvested, their roots can serve as food for prawns. Majority of the respondents (85%) reported that adopting RPVC increased the overall productivity. Farmers faced a variety of climatic hazards; ranked as: drought (86.3%) > erratic and sudden heavy rainfall (81.5%) > temperature fluctuation (69.6%) > salinity intrusion (67.2%) > storm (28.5%). The ecosystem services provided by RPVC helped farmers to mitigate the adverse impacts of these climate-induced challenges through ecosystem-based adaptation. Integrated RPVC has also enabled farmers to maintain a consistent cash flow throughout the year. By promoting the production of multiple commodities—rice, prawns, and vegetables—the system reduces the risk of financial destitution. Despite benefits, farmers also encountered several challenges in implementing RPVC including water shortage (85.2%), disease (73.5%), theft (60.4%), increased feed costs (70.7%), lack of information (65%), increased labor cost (58.8%), and not getting expected market value of farming products (63.2%). However, if these barriers are addressed, the integrated RPVC system holds significant potential to foster long-term socio-economic growth in the southwest region of Bangladesh.